2009
DOI: 10.1111/j.1523-1739.2009.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Protected Areas, Faiths, and Sacred Natural Sites

Abstract: Most people follow and are influenced by some kind of spiritual faith. We examined two ways in which religious faiths can in turn influence biodiversity conservation in protected areas. First, biodiversity conservation is influenced through the direct and often effective protection afforded to wild species in sacred natural sites and in seminatural habitats around religious buildings. Sacred natural sites are almost certainly the world's oldest form of habitat protection. Although some sacred natural sites exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
210
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(216 citation statements)
references
References 41 publications
4
210
1
1
Order By: Relevance
“…Sacred groves are community-preserved, often small, forest patches in which certain spiritual, cultural or religious values contribute to the conservation of biodiversity and ecosystem services (Berkes 2009;Dudley et al 2009;Ray et al 2014). Sacred groves may be remnants of earlier more continuous forests or planted or regenerated forest patches in non-forest landscapes (Bhagwat et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sacred groves are community-preserved, often small, forest patches in which certain spiritual, cultural or religious values contribute to the conservation of biodiversity and ecosystem services (Berkes 2009;Dudley et al 2009;Ray et al 2014). Sacred groves may be remnants of earlier more continuous forests or planted or regenerated forest patches in non-forest landscapes (Bhagwat et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…the entire Ethiopian highlands. This information is, however, urgently needed to enable the integration of these habitat patches into wider (global) conservation strategies (Dudley et al 2009) and to understand what actions must be undertaken to conserve these forests, which are known for their exceptionally high vertebrate and plant diversity, rich in narrow-range species (Burgess et al 2006). The spatial arrangement and patch characteristics of church forests are important because the viability of a population within a habitat fragment or patch depends, among other factors, on the number of patches, the size of the individual patches, the isolation of the patches and the edge effects associated with the shapes of the patches (Fahrig 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They occur in various forms and at various spatial scales, such as a single plant species Folke 2001, Kufer et al 2006), burial grounds (Mgumia andOba 2003, Wadley andColfer 2004), sacred groves Vartak 1974, Malhotra 2001), and even whole mountains or lakes used for religious worship (Maharana et al 2000, Castro and Aldunate 2003, Jain et al 2004, Xu et al 2005. Sacred sites have been under the protection of local people for their spiritual value for generations and might be the oldest forms of protected areas in human history (Dudley et al 2009). It has been shown that the traditional practice of sacred site worship may make significant contributions to protecting endangered species and conserving biodiversity (Decher 1997, Mgumia and Oba 2003, Bhagwat et al 2005a, 2005b, Bossart et al 2006, and few studies have documented the social mechanisms behind those traditional practices (Malhotra 2001, Tengö et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The fear of retribution, also reported by several researchers, is likely holding pastoralists in the study area from taking actions that can jeopardize their relations with their spirit protectors (Buchler et al 1980, Horne 2003Jones et al 2008;Boteroa et al 2014;Woodhouse et al 2015). Such actions consciously taken or unintentional sometimes are also known to have benefits to natural world (Jones et al 2008;Dudley et al 2009;Dominguez et al 2010).…”
Section: Internal Factorsmentioning
confidence: 98%